The question states that the Statue of Liberty is 30 times the height of a 154 centimeter person and asks how many meters tall the <span>the Statue of Liberty is.
This is basically asking us to find 30 times 154 centimeters and convert it to meters.
30 • 154 = 4620
This tells us that the </span>Statue of Liberty is 4,620 centimeters (cm) tall.
Now we must convert 4,620 cm to meters (m).
There are 100 cm in 1 m.
This means 100 cm = 1 m.
That means that meters are 100 times larger than centimeters.
With this in mind, we can divide the number of cm by 100 to convert it to m.
4,620 ÷ 100 = 46.2
That means that 4,620 cm is equal to 46.2 m.
The final answer:
If the Statue of Liberty is 30 times taller than 154 centimeters, then the Statue of Liberty is 46.2 meters tall.
So the answer is 46.2 meters.
Hope this helps!
Answer:
a) ![\large F(x,y)=(-\frac{y}{x^2+y^2},\frac{x}{x^2+y^2})](https://tex.z-dn.net/?f=%5Clarge%20F%28x%2Cy%29%3D%28-%5Cfrac%7By%7D%7Bx%5E2%2By%5E2%7D%2C%5Cfrac%7Bx%7D%7Bx%5E2%2By%5E2%7D%29)
b) ![\large \mathbb{R}^2-\{(0,0)\}](https://tex.z-dn.net/?f=%5Clarge%20%5Cmathbb%7BR%7D%5E2-%5C%7B%280%2C0%29%5C%7D)
c) the points of the form (x, -x) for x≠0
Step-by-step explanation:
a)
If φ(x, y) = arctan (y/x), the vector field F = ∇φ would be
On one hand we have,
On the other hand,
So
b)
The domain of definition of F is
i.e., all the plane X-Y except the (0,0)
c)
Here we want to find all the points such that
where k is a real number other than 0.
But this means
So, all the points in the line y = -x except (0,0) are parallel to the vector field F, that is, the points (x, -x) with x≠ 0
Answer:
116
Step-by-step explanation:
16+16=56/2=4
Well 24=4*6, and 35=7*5 not 6, so 4/7 doesn't = 24/35, so no
Answer:
Step-by-step explanation:
Simplifying
6 = 1 + -2n + 5
Reorder the terms:
6 = 1 + 5 + -2n
Combine like terms: 1 + 5 = 6
6 = 6 + -2n
Add '-6' to each side of the equation.
6 + -6 = 6 + -6 + -2n
Combine like terms: 6 + -6 = 0
0 = 6 + -6 + -2n
Combine like terms: 6 + -6 = 0
0 = 0 + -2n
0 = -2n
Solving
0 = -2n
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right.
Add '2n' to each side of the equation.
0 + 2n = -2n + 2n
Remove the zero:
2n = -2n + 2n
Combine like terms: -2n + 2n = 0
2n = 0
Divide each side by '2'.
n = 0
Simplifying
n = 0